Individual Investor Behavior in Sharia-Compliant Stock Investment Decisions on the Indonesia Stock Exchange - Ahmad Zikri Dwiatmaja; Rika Dwi Ayu Parmitasari; Nasrullah Bin Sapa (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
Sharia-compliant stock investment is increasingly popular, particularly among Generation Z and millennial investors. However, investment decisions are influenced not only by rational considerations, such as fundamental and technical analysis, but also by psychological factors and investor behavior. This study aims to analyze the effects of overconfidence, financial attitude, and risk tolerance on Sharia stock investment decisions on the Indonesia Stock Exchange, with Islamic financial literacy as a moderating variable. This study employs a quantitative approach using a survey method, in which data were collected through questionnaires distributed to Sharia stock investors. The data were analyzed using Structural Equation Modeling (SEM) to examine the relationships among variables. The results indicate that overconfidence, financial attitude, and risk tolerance have a positive and significant effect on investment decisions. Islamic financial literacy is found to moderate the relationships between financial attitude and investment decisions, as well as between risk tolerance and investment decisions, but does not moderate the relationship between overconfidence and investment decisions. These findings suggest that a strong understanding of Islamic financial literacy can help mitigate overconfidence bias in investment decision-making, enabling investors to behave more rationally when selecting Sharia-compliant stocks. Therefore, enhancing Islamic financial literacy through education and training is essential to support more prudent decision-making and to help investors avoid high-risk investments